Effects of the spectral properties of a panchromatic image on pan-sharpening simulated using hyperspectral data. (1st October 2016) - Matsuoka, Masayuki; Tadono, Takeo; Yoshioka, Hiroki
ABSTRACT: This study proposes a methodology for simulating pan-sharpening using hyperspectral (HS) data to evaluate the influence of the spectral properties (band position and band width) of panchromatic (PAN) data on the quality of pan-sharpened data. PAN images were generated from Airborne Visible/Infrared Imaging Spectrometer HS data by changing the position and width of the spectral waveband, and these images were subjected to pan-sharpening with multispectral (MS) bands, also generated from HS data. The qualities of pan-sharpened MS data were evaluated using five measures: erreur relative globale adimensionnelle de synthèse, weighted signal-to-noise ratio, universal image quality index, quality index based on local variance and objective image fusion performance measure. This methodology was applied to three pan-sharpening methods (Gram–Schmidt spectral sharpening, block-based synthetic variable ratio and generalised Laplacian pyramid with spectral distortion minimisation) to characterise the spectral and spatial qualities of pan-sharpened images. The results show that the pan-sharpened images were affected by the spectral properties of the PAN data to varying degrees depending on the pan-sharpening method used and the land cover type. Better-quality images were obtained if the spectral properties of the PAN and MS bands were similar. No one spectral property was identified as best for all MS bands. This methodology will be helpful for the evaluation of the spectral behaviour of pan-sharpening methods, the development of new pan-sharpening methods and the design of new sensors suitable for pan-sharpening.